Magnitude and Spatial Distribution of Bioecological Carrying Capacity in Sleman Regency - Andri Kurniawan; Farhan Azis; Martina Ayu Sejati (Universitas Negeri Semarang, 2023)
The objectives of the research were (1) to analyze the value of the biocapacity and ecological footprint in Sleman Regency; (2) to measure and analyze the value and spatial distribution of bioecological carrying capacity in global hectare units (global hectare); and (3) formulating the direction of development and control of development based on the class of bioecological carrying capacity. The research was conducted using a quantitative approach through processing and analyzing secondary data from various sources. Secondary data that is processed is data at the village level. The determination of the bioecological carrying capacity is based on the calculation of the ecological footprint as a manifestation of the level of consumption that reflects the population’s needs, and biocapacity which is the embodiment of the aspect of land use in providing resources. Based on the current conditions and land use composition, the Sleman Regency area only has a biocapacity value or can only support each resident with a land area of 0.20 hectares global/person. On the other hand, the value of the ecological footprint or the level of need reaches 0.279 global hectares/person. Thus, the bioecological carrying capacity in Sleman Regency has a value of 0.87 or a deficit of 0.078 hectares globally per capita. That shows that the Sleman Regency area has experienced an overpopulation with current productivity and land use. The low carrying capacity of bioecology in Sleman Regency is also reflected in the fact that most villages are classified as having low carrying capacity, reaching 68%. However, many villages still have a high bioecological carrying capacity (1.2), especially in the northern and western parts of the Sleman Regency. The primary attention needs to be devoted to villages with a low bioecological carrying capacity, which is 58 villages. In these villages, the direction of development needs to be emphasized in controlling land use change and increasing productivity, limiting business scale, and controlling population growth rates.